Radiosynovectomy for the treatment of rheumatoid arthritis of the elbow - Rozeboom, S.; Dörr, U.; Bihl, H. (Nuklearmedizin - NuclearMedicine, 2001)
The Aim of this retrospective study was to evaluate the efficiacy of radiosynovectomy (RSO) in patients with rheumatoid elbow arthritis. Patients and Methods: 40 joints of 31 patients were evaluated. At the time of therapy, patients had been suffering from elbow arthritis for 17.5 months (2-72 months). 95% of the joints (n = 38) had severe dally pain or continuous pain, 97.5% (n = 39) had moderate to severe limitation of the mobility and 10% (n = 4) had severe swelling. RSO was performed by intraarticular injection of 74 MBq colloidal rhenium-l 86 and 15 mg triamcinolonehex-acetonide. Before and six to 26 months after therapy (median follow-up 14.7 months) severity of the patients pain, mobility and swelling (transferred to a scoring system) were determined with a standardised questional. A clinical re-evaluation, along with an ar-throsonographical follow-up was performed in 28 joints. Results: A “good to very good” overall long-term response was achieved in 80% (n = 32) of the treated joints and a temporary response in 10% (n = 4). Only 10% (n = 4) had a non-satisfactory response due to advanced articular destruction. The range of motion for flexion-extension increased from 103.8 ± 20.0 degrees to 144.0 ±12.8 degrees (p <0.001). The respective scores for articular pain, impaired mobility and swelling decreased significantly (pain from 3.15 to 0.82, impaired mobility from 3.15 to 0.82, swelling from 2.40 to 0.65; p <0.00U. No deterioration or complication occurred. The effects lasted throughout the entire follow-up time for 36 joints (90%). Conclusion: For patients with rheumatoid involvement of the elbow joint, radiosynovectomy results in a significant decrease of articular pain and improvement of objective parameter, i.e. joint mobility. Thus, radiosynovectomy represents a feasible and effective therapeutic option for elbow arthritis.
Keywords: Radiosynovectomy; rhenium-186; rheumatoid arthritis; elbow